6x(4x+3)=0

Simple and best practice solution for 6x(4x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x(4x+3)=0 equation:


Simplifying
6x(4x + 3) = 0

Reorder the terms:
6x(3 + 4x) = 0
(3 * 6x + 4x * 6x) = 0
(18x + 24x2) = 0

Solving
18x + 24x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '6x'.
6x(3 + 4x) = 0

Ignore the factor 6.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(3 + 4x)' equal to zero and attempt to solve: Simplifying 3 + 4x = 0 Solving 3 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 0 + -3 4x = 0 + -3 Combine like terms: 0 + -3 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75

Solution

x = {0, -0.75}

See similar equations:

| 2(2)-3y=-9 | | -50+x=-10 | | 40x-6=9 | | -4(x+3)=x+8 | | 6x(4x-1)=0 | | 5x-10x=x-12 | | 172-6x=6x+16 | | -(-2x)=(-88) | | 2(x+4)=5x-1 | | 6p+12=4p | | -4x+12=x+17 | | 12-9x=52-16x | | 3x-7=-4x | | 3x-7=-1 | | -x-6=-2 | | (x^2-9)(x+4)=0 | | 18+x=-2 | | X^4+6x=0 | | 5x-7=103 | | (x^2-2)(x^2+3)=0 | | 170-5x=6x+5 | | 5x+1=3x+13 | | -4x^2-4x+3=0 | | 6p+3=3p+12 | | q=4.5-0.5 | | P^2-6p+8= | | 5x-2=x-14 | | 58-5=8+19 | | 2(x-12)=3(x-8) | | -9x^2=100 | | 6x^2+486=0 | | 15+3x=-3 |

Equations solver categories